A systems-level framework for drug discovery identifies Csf1R as an anti-epileptic drug target - Srivastava,P; van,Eyll J; Godard,P; Manuela,M; Delahaye-Duriez,A; Van,Steenwinckel J; Gressens,P; Danis,B; Vandenplas,C; Patrik,F; Leclercq,K; Mairet-Coello,G; et al. (Nature Communications, 2018)
The identification of drug targets is highly challenging, particularly for diseases of the brain. To address this problem, we developed and experimentally validated a general computational framework for drug target discovery that combines gene regulatory information with causal reasoning (“Causal Reasoning Analytical Framework for Target discovery”—CRAFT). Using a systems genetics approach and starting from gene expression data from the target tissue, CRAFT provides a predictive framework for identifying cell membrane receptors with a direction-specified influence over disease-related gene expression profiles. As proof of concept, we applied CRAFT to epilepsy and predicted the tyrosine kinase receptor Csf1R as a potential therapeutic target. The predicted effect of Csf1R blockade in attenuating epilepsy seizures was validated in three pre-clinical models of epilepsy. These results highlight CRAFT as a systems-level framework for target discovery and suggest Csf1R blockade as a novel therapeutic strategy in epilepsy. CRAFT is applicable to disease settings other than epilepsy.